The Role of Gut Microbiome Dysbiosis in the Pathogenesis of Neurodegenerative Diseases (Alzheimer’s Disease, Parkinson’s Disease, and Multiple Sclerosis) – A Comprehensive Review - Kruszewska, Natalia; Hanna Pietruszewska; Oliwia Sędziak; Sabina Skrzynecka; Urszula Borucińska (Quality in Sport, 2025)
Background: The gut microbiome interacts with the nervous system through the gut–brain axis (GBA), which is essential for understanding mechanisms contributing to neurodegenerative diseases via neuronal, endocrine, and immune pathways. Gut dysbiosis disrupts microbial balance and is associated with Alzheimer’s disease (AD), Parkinson’s disease (PD), and multiple sclerosis (MS), contributing to impaired blood–brain barrier integrity and protein aggregation. Effective treatment is crucial to maintain patients’ independence, daily function, and quality of life while reducing long-term healthcare costs. Aim: This study aimed to synthesize and critically evaluate recent evidence on the role of the gut microbiome and its metabolites in AD, PD, and MS, and to discuss potential diagnostic and therapeutic implications within the GBA. It also highlights the relevance of these findings for health education and future interventions. Materials and methods: Studies on the impact of the gut microbiome on neurodegenerative diseases were analyzed using PubMed, Scopus, and Web of Science. The search included terms such as “gut microbiome,” “dysbiosis,” “gut–brain axis,” “Alzheimer’s disease,” “Parkinson’s disease,” and “multiple sclerosis,” covering publications from 2018 to 2025. Results: Altered levels of short-chain fatty acids (SCFAs), lipopolysaccharides (LPS), and biogenic amines influence neuroinflammation, blood–brain barrier function, and protein aggregation. Preliminary data suggest that modulating the microbiome may help regulate inflammatory responses. Conclusions: Evidence indicates that the gut microbiome plays a significant role in neurodegenerative disease development. Dysbiosis may serve as a biomarker and therapeutic target. Integrating gut health into preventive programs may enhance effectiveness and support early detection and management strategies.